Planning, Implementing and Evaluating a Health Promotion Program - Jansz, Janis (Vineyard Publishing, 2011)
Health promotion programs can be used in a workplace to improve employees' health. This chapter describes the reasons to have a workplace health promotion program, how to plan, advertise, implement and how to evaluate a chosen health promotion program.